2017
DOI: 10.1007/s00210-017-1447-3
|View full text |Cite
|
Sign up to set email alerts
|

The effect of vitamin U on the lung tissue of pentyleneterazole-induced seizures in rats

Abstract: The aim of this study is to investigate the therapeutic effects of vitamin U (Vit U) on lung tissue of pentyleneterazole (PTZ)-induced seizures in rats. Sprague Dawley male rats were randomly divided into four groups as follows: control (0.9% NaCl given, intraperitoneally); Vit U (50 mg/kg/day, for 7 days by gavage); PTZ; (60 mg/kg one dose, intraperitoneally); and PTZ + Vit U (in same dose and time). At the end of the experiment, lung tissues were taken and examined biochemically and cytologically. Lipid pero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 50 publications
1
11
0
Order By: Relevance
“…[38] Several studies revealed that excessive generation of free-radical intermediates including reactive oxygen species (ROS) are associated with VPA administration, possibly as a consequence of VPA biotransformation, alterations in GSH homeostasis, and/or depletion of cofactors required for antioxidant defense. [14,39,40] Additionally, MPO produces ROS such as hydroxyl radicals, singlet oxygen, and ozone, which are the most important and clinically relevant oxidants. [41] Oztay et al [42] noted that ROS pro- Thus, it is accepted that increased LPO and MPO activity in tissues are excellent markers of induced oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[38] Several studies revealed that excessive generation of free-radical intermediates including reactive oxygen species (ROS) are associated with VPA administration, possibly as a consequence of VPA biotransformation, alterations in GSH homeostasis, and/or depletion of cofactors required for antioxidant defense. [14,39,40] Additionally, MPO produces ROS such as hydroxyl radicals, singlet oxygen, and ozone, which are the most important and clinically relevant oxidants. [41] Oztay et al [42] noted that ROS pro- Thus, it is accepted that increased LPO and MPO activity in tissues are excellent markers of induced oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…Vit U attenuated oxidative stress by increasing activities of antioxidant enzymes in the lens, liver, and kidney of rats. Recently, Oktay et al [ 14 ] reported the protective role of Vit U against oxidative stress‐induced lung damage, which may occur during seizures in epileptic rats, by increasing GSH level and activities of SOD and CAT. In the current study, Vit U also diminished VPA‐induced oxidative damage in rat lungs by increasing the GSH level and activities of GST and GPx in addition to activities of SOD and CAT.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This might be associated with the duration of administration of MMSC (three consecutive days). Oktay et al, stated that the administration of MMSC (50 mg/kg/day) to intact animals for 7 days caused an insignificant elevation of NO levels (7). In GalN injected groups, the levels of NO were remarkably elevated as compared to intact rats.…”
Section: Discussionmentioning
confidence: 99%
“…It is being studied as a source of anti-peptic ulcer dietary factors. As of its clinical importance, MMSC had several biofunctions such as cytoprotective agents against gastrointestinal disorders (6) and anti-epileptic effects (7). Besides, MMSC plays an important role by acting as a radical scavenger, as well as anti-fibrotic and anti-inflammatory agent under oxidative stress conditions (8).…”
Section: Introductionmentioning
confidence: 99%